Lunar Ionosphere in the Geotail Region as Observed by Chandrayaan-2 Orbiter Using Two-way Radio Occultation Measurements - Keshav R. Tripathi; R. K. Choudhary; K. M. Ambili (The Astrophysical Journal Letters)
The study presents the first electron density profile of the Lunar ionosphere when the Moon is inside the geomagnetic tail region. This observation used S -band telemetry and telecommand radio signals in a two-way radio occultation experiment from Chandrayaan-2 (CH-2) orbiting the Moon. The radio signals were tracked using an 18 m diameter antenna at the Indian Deep Space Network (IDSN). The IDSN served as an active source for generating and receiving the radio signal, while the onboard oscillator on CH-2 was used as a passive receiver and transmitter. The transmitted radio signal passed twice through the lunar plasma medium before reaching the receiver end. The study found a high electron density of approximately ∼2.5 × 10 ^4 per cm ^−3 close to the surface of the Moon. Three-dimensional lunar ionospheric model simulations show that to achieve such high plasma density, the plasma should be in photochemical equilibrium, which is possible inside the geomagnetic tail only in the presence of lunar crustal magnetic fields. The model also introduced a localized reduction in Ar and Ne neutral density to align with previous observations near the lunar pole.